Psychological Stress among Mothers of General Secondary Education Students in Light of some Variables - A Field Study in Lattakia City - فاطمة شغري; ليلى شريف; هنادي حسون (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the level of psychological stress among the mothers of general secondary education students in Lattakia city, as well as to reveal differences in the level of psychological stress among them according to the following variables (the mother’s work, the student’s gender, the academic grade, and the student’s branch). The research sample included (286) mothers of general secondary education students. To achieve the purpose of the research, the descriptive analytical method was used, and a measure of psychological stress among mothers was applied, which consisted of (36) items, including the following dimensions (family, economic and emotional stress). The results of the research showed that the level of psychological stress among mothers of general secondary education students in Lattakia city was high, and the two dimensions (family and economic stress) were at a high level, while the emotional stress dimension was at a middle level. The results also showed that there was a difference in the level of psychological stress. Among mothers, according to the mother’s work variable, in favor of the working mother, and according to the student’s gender variable, in favor of males, as well as according to the academic grade variable, in favor of third-year secondary school students also according to the student branch variable, in favor of scientific branch students. Based on these results, several recommendations were made, the most important of which are: building counseling programs to reduce the level of psychological stress on students’ mothers, and conducting studies on methods of coping with their psychological stress.